Unilateral biportal endoscopic foraminotomy and diskectomy combined with piezosurgery for treating cervical spondylotic radiculopathy with neuropathic radicular pain - Zhang, Peng; Jin, Yanghui; Zhu, Bo; Zheng, Mingfeng; Ying, Xiaozhang; Zheng, Qi (Frontiers in Neurology, 2023)
Objective: Unilateral biportal endoscopy (UBE) represents a relatively recent development in minimally invasive spine surgery. This study aimed to evaluate the efficacy and safety of UBE foraminotomy and diskectomy combined with piezosurgery for treating cervical spondylotic radiculopathy (CSR) with neuropathic radicular pain. Methods: We retrospectively analyzed the outcomes in 12 patients with CSR who underwent UBE foraminotomy and diskectomy combined with piezosurgery. The intraoperative blood loss, operative time, visual analog scale (VAS) scores for the neck and arm, neck disability index (NDI) scores, and complications were recorded. Results: Postoperative VAS scores of the neck and arm and NDI scores were significantly improved. Additionally, postoperative CT scan revealed adequate enlargement of cervical canal and nerve root. No specific complications occurred during surgery and the immediate postoperative period. Conclusions: This primary study indicated that the UBE foraminotomy and diskectomy with piezosurgery is a promising technique for treating cervical spondylotic radiculopathy with neuropathic radicular pain.